(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
The aim of this this research is describe the competences of the waitress team in the General Section of the Regional Secretariat of Magelang City, find the factors that cause the competency of the waitress team to not up to standard, and formulate steps so that the competency of the waitress team is up to standard. This research uses a qualitative method, to determine the competence of the waitress team, constraints and solutions for solving them. The data were collected through literature study, observation and interviews. The results suggested that the factors which caused the competency of the waitress team were not up to standard contains incompatibility of educational background, the recruitment process was not well organized, there was no operational standard (SOP), lack of knowledge about cooking and housekeeping, and the character of the waitress team was not yet formed. Efforts were made to overcome this problem by involving the team of waiters in the training program, improving the recruitment system, developing operational standards (SOP), and providing training on service excellence.